Effect of Cutting Parameters on Wear and Surface Roughness of Stainless Steel (316L) Using Milling Process - Khleif, Ali Abbar; Abdullah, Mostafa Adel (Nahrain University College of Engineering Journal, 2017)
Flank wear width is generally recognized as the key indicator for tool life. In the milling process, several factors that influence on the wear of the tool) the material of workpice, the tool material, cutting conditions, the shape of a tool, machining time). In the experiments stainless steel 316L was used and cutting parameter with constant cutting tool type, cutting feed ,depth of cut and four spindle speeds(350,550,930 and 1100) rpm. The cutting tool wear was measured using optical microscope. The results showed an increase in cutting speed lead to decreases surface roughness (2.648,2.285,1.878 and 1.526) ?m respectively with constant machine parameter and give indicating for tool wear which increase with the increase roughness of production surface.Key words: , ,, .